Seroprevalence of diphtheria IgG antibodies among 5-20 years old in diphtheria affected regions during 2018-19: Evidence in support of the revised National Vaccine Policy for diphtheria in India - Bindu R. Madhavi; Anitha Deva; Mahendra M. Reddy; P.M. Beena; S.N. Vijay Kumar (Elsevier, 2024)
Background: Diphtheria continues to be a public health problem in India as it is re-emerging in several regions of the country. In recent times, apart from preschool-aged children, diphtheria outbreaks are seen to affect older children and adults. The present study was conducted to determine the immunity against diphtheria among the 5-20 years age group in a population from diphtheria-affected regions of Kolar. Methods: This facility-based cross-sectional study was conducted in six diphtheria-affected regions of Kolar district, Karnataka, India among the population aged between five and 20 years from June 2018 to December 2019. A total of 337 participants who sought health care from the primary health centres were included in the study and the IgG antibody titres against diphtheria were estimated by using enzyme-linked immunosorbent assay (ELISA). Chi-square test was done to see the association of variables with antibody titres to diphtheria. Results: In the present study, among the 337 study participants; 53.7 % of the participants had full protection, 35.6 % had basic protection and 10.7 % did not have any protection and were susceptible to diphtheria. None of the study participants had reliable long-term protection against diphtheria (>1.0 IU/ML). Conclusion: About half of the study participants from the diphtheria-affected regions belonged to the susceptible category and the basic protection category. Only 53.7 % of the participants showed full protection against diphtheria. This strongly advocates for the changes made in the National Vaccine Policy in India for the adoption of booster doses of vaccination against diphtheria in the population.